'How can the governance of communities that care interventions be enhanced by understandings of community development?': a case study in rural Australia. (28th April 2020) - Downey, Heather; Threlkeld, Guinever
Abstract: Communities That Care (CTC) is an evidence-based social development strategy that uses a structured process of intervention based on the evidence about risk and protective factors in communities. CTC uses particular governance groups as central instruments in a process that aims to build the capacity of communities to enhance the lives of young people. This article reports findings from a formal evaluation which used a collaborative governance lens to examine governance of the application of CTC in a small rural Australian community. Specifically, the evaluation focussed on the perspectives of members of the governance structures concerning CTC's operation and value at the interstice of youth and rural disadvantage. Findings suggest the potential within CTC to achieve sustainable community change may be enhanced through an endogenous governance approach that recognizes and develops community residents' potential for leadership. The CTC strategy is now utilized internationally. This article offers important insights for practitioners, organizations and communities considering implementing this approach.